New horizons in the ageing autonomic nervous system: orthostatic hypotension and supine hypertension. (2nd August 2022) - Dani, Melanie; Taraborrelli, Patricia; Panagopoulos, Dimitrios; Dirksen, Andreas; Torocastro, Miriam; Sutton, Richard; Lim, Phang Boon
Abstract: Blood pressure regulation is an automatic, moment-by-moment buffering of the blood pressure in response to physiological changes such as orthostasis, exercise and haemorrhage. This finely orchestrated reflex is called the baroreflex. It is a regulated arc of afferent, central and efferent arms. Multiple physiological changes occur with ageing that can disrupt this reflex, making blood pressure regulation less effective. In addition, multiple changes can occur with ageing-related diseases such as neurodegeneration, atherosclerosis, deconditioning and polypharmacy. These changes commonly result in orthostatic hypotension, hypertension or both, and are consistently associated with multiple adverse outcomes. In this article, we discuss the healthy baroreflex, and physiological and pathophysiological reasons for impaired baroreflex function in older people. We discuss why the common clinical manifestations of orthostatic hypotension and concomitant supine hypertension occur, and strategies for balancing these conflicting priorities. Finally, we discuss strategies for treating them, outlining our practice alongside consensus and expert guidance.